ISSUES OF FORMULATION OF FINANCIAL RISK CLASSIFICATION (Marketing Journal, 2025)
This article describes the need to develop a risk classification in managing financial risks and its advantages, the importance of classification in maintaining risk statistics, and the issues of using classification in the public finance management system. Also presented are proposals aimed at the composition and use of the classification of financial risks as an integral part of state financial contr ol.
Keywords: financial risks; financial offenses; state financial control; state budget; preliminary control; current control; exchange rate; interest rate; regulatory legal acts